HISTOPATHOLOGICAL STUDY OF ENDOMETRIUM IN ABNORMAL UTERINE BLEEDING IN REFERENCE TO DIFFERENT AGE GROUPS, PARITY AND CLINICAL SYMPTOMATOLOGY - Kunda, Jagadale; Anupam, Sharma (International Journal of Clinical and Biomedical Research, 2015)
Background: Abnormal uterine bleeding is the commonest presenting symptom and major gynecological problem responsible for as many as one-third of all out patient gynecologic visit. An understanding of the varieties in the normal morphological appearance of the endometrium provides an essential background for the evaluation of endometrial pathology. Aims: To study the histopathology of endometrial biopsies in patients presenting with abnormal uterine bleeding and its correlation with age, parity and bleeding pattern Methods: This was a study done at tertiary care hospital from 2012-2014. Endometrial biopsies obtained from 100 cases of patients presenting with abnormal uterine bleeding were studied followed by correlation of endometrial histopathology with parity, age and bleeding pattern. Results: The most common age group presenting with abnormal uterine bleeding was 41-50 years (31%).The commonest pathology was proliferative endometrium (29%).The commonest bleeding pattern was menorrhagia (88%) and highest incidence was seen in multiparous women(58%).Conclusion: Endometrial biopsy should be recommended during the workup of patients presenting with abnormal uterine bleeding to exclude organic pathology of endometrium KEYWORDS: Abnormal uterine bleeding; Menorrhagia; Endometrium; Endometrial biopsy.